A kernel average misorientation evaluation of surface alterations caused by angled droplet impingements - Jakub Poloprudský; Alice Chlupová; Štěpán Gamanov; Dagmar Klichová; Gabriel Stolárik; Akash Nag; Sergej Hloch (Engineering Science and Technology, an International Journal)
The droplet impact angle on the solid surface plays a crucial role in the erosion development, which is critical in structural applications. In the present study, a pulsating water jet with a frequency of 40 kHz generated droplets impacting the surface of steel. The number of droplet impingements ranged from 20,000 to 400,000 (0.5–10 s). The impact angle was 90°, 75°, 60°, 45°. The exposure longer than 3 s caused material removal. The exposure of 3 s or less caused surface roughening. The SEM observation of the roughened surface was supplemented by the roughness, and the kernel average misorientation analysis. Proposed segmentation delineates the non-uniformity of erosion and outlines the damage contours, which helps predict the location of material removal onset.